Multiple-image encryption algorithm based on DNA encoding and chaotic system - Zhang, Xiaoqiang; Wang, Xuesong (Multimedia tools and applications, 2019)
Under the Internet platform, the digital images are widely applied in many fields at present. To protect the content of multiple images, a new multiple-image encryption (MIE) algorithm based on Deoxyribonucleic acid (DNA) encoding and chaotic system is proposed in this paper. Different from the traditional image encryption algorithms, the permutation and diffusion of the new algorithm is manipulated on the three-dimensional DNA matrix. Firstly, k plain images are combined into a big image which is then encoded with the DNA codes; secondly, the big image is scrambled by a chaotic sequence; thirdly, the big image is segmented into k images with the same size of the plain images, and they are diffused by a chaotic image encoded with the DNA codes; finally, k encrypted images are obtained after the DNA decoding. SHA-256 hash value of the plain images is employed to calculate the initial values and control parameters of the chaotic systems. Experimental results and algorithm analyses show that the new encryption algorithm has excellent encryption effect and high security.